Translucent zirconia: modifications and current classifications – a review / Muhammad Nur Izham Khairuddin, Aini Hayati Abdul Rahim and Mohamed Ibrahim Abu Hassan - Khairuddin, Muhammad Nur Izham; Abdul Rahim, Aini Hayati; Abu Hassan, Mohamed Ibrahim (Faculty of Dentistry, 2025)
Zirconia ceramics have undergone several modifications to improve its optical properties which expanded its indication in many clinical scenarios. Newer generations of zirconia with higher translucency and multi-layer configuration combined with high strength and biocompatibility are being developed continuously in the market. Optical properties of zirconia particularly translucency can be improved through several modifications’ techniques that utilise the understanding of its isotropic and polymorphism attributes. Various types of zirconia are now available in the market which can be classified into different parameters for selection and further aid clinicians in making accurate clinical decision making. The expanded clinical application of zirconia ceramics has been facilitated by advancements in their translucency. This progress stems from an enhanced comprehension of zirconia's intrinsic properties, which has enabled the development of innovative approaches to improve its transparency and aesthetic characteristics.